Manajemen Akat Maal di Kota Makassar : Telaah atas Upaya Produktivitas Zakat - St Habibah; Muammar Bakri; Sabri Samin; Hamzah Hasan; Juhasdi Susono (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This article aims to determine the Urgency of BAZNAS Institution Management, To find out the management of Muztahik criteria determination in getting Zakat Maal, To find out the service system of BAZNAS officers, To find out the management of Maal Zakat management in productivity in Makassar City, To find out the management of Muztahik empowerment in improving their welfare, and To determine the productivity of Zakat Maal in improving the welfare of Muztahik in Makassar City. Data analysis technique used In analyzing the data the method used is a descriptive qualitative. Research Results Show Makassar City Baznas Institution is considered important in managing zakat maal but it has not been given maximum attention by the Makassar city government and the existing Service System in Makassar City Baznas has increased from year to year only to the extent of the institution of Baznas Not until UPZ (Zakat Collecting Unit) which is spread in several districts of Makassar city